PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SATUAN LUAS DENGAN ALAT PERAGA SPEKTRUM SATUAN (Studi Kelas V di SDN Betet 3 Kec. Pesantren Kota Kediri) - Samidi, Samidi (Universitas Nusantara PGRI Kediri, 2016)
Abstract: The function and role of the teacher as facilitator and motivator has enormous influence in improving activity and student learning outcomes. The teacher's role in the selection of models, approaches, strategies, techniques and tactics appropriate learning is crucial to the success of student learning. In general, the class V student learning outcomes is still low, less learning activities, passive learning. The average value of the class in the previous KD unsatisfactory at only 62. To overcome these researchers chose Quamtum Teaching learning model which is famous for the term T-A-N-D-N-R. The purpose of this research is to increase the activity and results of learning mathematics in students through a learning model Quamtum Teaching with props Spectra Unit .. While the benefits to be obtained from this study is that this method is expected to increase the activity and student learning outcomes, can be an alternative learning methods in the classroom and learning innovation developmentThis research is a classroom action research, which is conducted independently. The subjects were 45 students of class V in Betet 3 district. Pesantren - Kediri. The study consisted of two cycles, each cycle consisting of two meetings with the allocation of time for each meeting is 2 x 35 minutes. Data collection techniques using observation and tests. Observation guide used every learning took place, questionnaires and tests used each cycle ends. Interview guides used at the end of the second cycle and field notes made every learning takes place.Based on the research results, we concluded that the implementation of learning mathematics by using T-A-N-D-u-R (Quantum Teaching) with props